POLITICS OF IDENTITY AND ITS CHALLENGES FOR DEMOCRATIC GOVERNANCE IN NIGERIA - Shuaib Olarewaju Moyosore (International Studies Journal)
The study attempts to analyze the challenges identity politics pose to democratic governance and Nigeria's attempt at national development. The paper contends that a better understanding of the interplays militating against the country's quest for democratic sustenance is discernable from manipulation of the country's diversity by the political elites through varied means. To this end, the conspiracy theory was adopted for this article. The research methodology consists of analysis and synthesis of secondary sources such as diverse literatures as well as primary source derived from discussions with some Nigerians. The analysis reveals that the actions and inactions of the leadership decipher the conspiratorial attempt of the political elites to gain vantage position or sustain their existing leadership positions. The paper recommends adherence to the rule of law, moral uprightness and selflessness as the cure for these challenges.